Influence of vigor, seed diameter and sowing depth on initial soybean establishment (Research, Society and Development, 2023)
Brazil is currently the largest producer of soy in the world, a crop that has a growing production volume and an important role for the country's economy. There are many factors involved in the success of this crop and this work aimed to evaluate the influence of vigor, seed diameter and sowing depth on the initial establishment of soybean plants. An experiment was conducted in a completely randomized design in a factorial arrangement (4x2x2), with four vigor ranges (70, 75, 85 and 95%), two seed sizes (sieves: 5.5 and 6.5 mm) and two seed depths. of sowing (0.03 and 0.06 m). Sowing was carried out in plastic trays filled with washed coarse sand and the experimental period lasted until the phenological stage V4. The following variables were analyzed: % of emergence, time to emergence, time to enter V4, height, volume of roots and fresh biomass: roots, shoots and the entire plant. Seed diameter did not influence the analyzed variables. The sowing at a depth of 0.06 m of seeds with 70% of vigor prevented the emergence of soybean seedlings. Seeds with vigor greater than 70% showed a higher percentage of emergence when sown at 0.03 m. Sowing at a depth of 0.06 m reduces the % of emergence, increases the time for emergence, reduces the number of days for the plants to reach the phenological phase V4 and decreases the height of the plants, the volume of roots, the total fresh biomass, shoots and roots.